Linguistic commentaries on the „Verzeichnis veralteter oder wenig bekannter litauischer Wörter“ collected by Gottfried Ostermeyer in Lithuania Minor (Kleinlitauen) - Ackermann, Katsiaryna (Baltistica, 2016)
The present article introduces a list of glosses to a collection of Lithuanian protestant spiritual hymns, compelled by Gottfried Ostermeyer, one of the prominent intellectuals and promoter of the Lithuanian culture and language of the 18th century in Lithuania Minor. The glossary was intended to facilitate the understanding of certain older or less known expressions, as Ostermeyer put it ‘obsoleta und minus cognita’, and due to political disputes among the intellectual community in East Prussian Lithuania Minor at the time of their publication fell into oblivion. The paper discuses a more or less random selection of twenty entries from the glossary, focusing on their dialectal features, semantic and morphological divergence from existing derivatives of the same root, and pays special attention to the derivational history and cross-IE cognates.Judging by the material studied in the paper the Lithuanian spoken idiom of the 17th-18th c. appears to be very vivid in onomasiology, creative in the usage of morphological means and still in possession of certain roots already gone in the dictionaries of the late 19th century and scarcely perceivable in the modern paramount linguistic database of LKŽ.
Keywords: Lithuanian; East Prussia; Lithuania Minor; Gottfried Ostermeyer; glossary